Self-Evaluation in a Clinical Setting to Develop Nursing Students’ Clinical Judgment (International Journal of Studies in Nursing, 2017)
Background: The Lasater clinical judgment rubric is based upon Tanner’s clinical judgment model for developing clinical judgment and the incorporation of the Benner Novice to Expert theory. The Lasater clinical judgment rubric has been used in nursing programs at the baccalaureate level and with simulation exercises. Method: In this study, the Lasater clinical judgment rubric was used to compare instructor and associate degree nursing students’ evaluations in an acute care setting during their first nursing care rotation. Data analysis included a split-plot ANOVA with repeat measures. A sample size of 16 students yielded an effect size of .40 with  = .001. Results: There was no significant difference in mean scores between the five administrations of the assessment with different groups. Conclusion: The interactions between the evaluator and the scores over time were consistent between groups. Development of student’s ability to use self-evaluation, introspection, and self-awareness skills are foundational for thinking that is more complex.